Clinical Trials Facing “Serious Adverse Events” during the Ongoing COVID-19 Pandemic - Parikh, Purvish M; Mehta, Prashant; MVT, Krishna Kumar; Babu, K Govind (Indian Journal of Medical and Paediatric Oncology, 2020)
Aims and Objectives: The ongoing COVID-19 pandemic is having a profound impact on the current clinical trials. We wanted to document the extent of the disruption amongst Indian clinical trial sites. Materials and Methods: We conducted an online survey among oncologists in India with active trials to document their experience with challenges and novel solutions. Results: A total of 60 oncologists replied of which 40 had ongoing trials with open recruitment. Majority of them had stopped screening (55%) and recruitment (62.5%). Almost half of the sites did not have adequate infrastructure (47.5%). Almost all the sites had enrolled patients worried about the impact of COVID-19 on their health outcome (up to 87.5%). The majority of sites had problems with adherence to study schedule of events (87.5%) and administration of study medication (42.5%). A total of 55% of the sites had provided the option of virtual visits. Both investigators (75%) and sponsors/contract research organizations (67.5%) had reached out to each other to maintain study integrity. More than half the centers had difficulty related to adverse events and serious adverse events (documentation and reporting; up to 75%). Discussion: Regulatory authorities in several countries have announced guidelines on the conduct of clinical trials during the COVID-19 pandemic. Whether the disruption lasts for a short or long time, its impact on clinical trials is going to be irreparable.
Keywords: Compliance; lockdown; recruitment; research; standard operating procedures